Concentration, Coagglomeration and Spillovers: The Geography of New Market Firms in Germany - Dirk Dohse; Sven-Christian Steude (European Regional Science Association (ERSA), 2003)
The Neuer Markt, launched in 1997 by Deutsche Börse, the German stock exchange, is Europe's closest equivalent to the Nasdaq, the US high-tech oriented stock market. Although the New Economy in Germany is not restricted to Neuer Markt firms one may argue that these firms and their employees form the spearhead of Germany's New Economy. In the current paper we employ the `dartboard approach' pioneered by Ellison and Glaeser to analyse the spatial concentration of New Economy employment in Germany, the coagglomeration of firms belonging to different sub-sectors of Neuer Markt and the (intraregional) spillovers between different high tech industries. We refine the analysis by differentiating between Neuer Markt firms in general and New Economy firms in a more narrow sense, and we compare their spatial distribution with the structure of the `traditional economy' as well as with the spatial distribution of other innovative activities such as patent applications or R&D. Key Words: Geographic concentration, New Economy, Neuer Markt, Dartboard Approach JEL Classification: G19, O30, O18, R11
Keywords: 330